2004
DOI: 10.1038/sj.onc.1207827
|View full text |Cite
|
Sign up to set email alerts
|

Parity-induced mammary epithelial cells facilitate tumorigenesis in MMTV-neu transgenic mice

Abstract: Using a Cre-lox-based genetic labeling technique, we have recently discovered a parity-induced mammary epithelial subtype that is abundant in nonlactating and nonpregnant, parous females. These mammary epithelial cells serve as alveolar progenitors in subsequent pregnancies, and transplantation studies revealed that they possess features of multipotent progenitors such as self-renewal and the capability to contribute to ductal and alveolar morphogenesis. Here, we report that these cells are the cellular target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
108
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 18 publications
11
108
0
Order By: Relevance
“…Using the mouse model of HER2 breast cancer, mouse mammary tumor virus (MMTV)-driven ErbB2 (homolog of human HER2/ neu), 53 PI-MECs were shown to be cellular targets of HER2-mediated oncogenesis. [54][55][56] Indeed, ErbB2 tumorigenesis in mice increases with parity, and targeted removal of PI-MECs in vivo reduced tumor incidence in ErbB2 mice. [55][56][57] Likewise, clinical studies demonstrate that women during or right after pregnancy (when the number of PI-MECs is highest) have increased susceptibility for HER2 breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the mouse model of HER2 breast cancer, mouse mammary tumor virus (MMTV)-driven ErbB2 (homolog of human HER2/ neu), 53 PI-MECs were shown to be cellular targets of HER2-mediated oncogenesis. [54][55][56] Indeed, ErbB2 tumorigenesis in mice increases with parity, and targeted removal of PI-MECs in vivo reduced tumor incidence in ErbB2 mice. [55][56][57] Likewise, clinical studies demonstrate that women during or right after pregnancy (when the number of PI-MECs is highest) have increased susceptibility for HER2 breast cancer.…”
mentioning
confidence: 99%
“…[54][55][56] Indeed, ErbB2 tumorigenesis in mice increases with parity, and targeted removal of PI-MECs in vivo reduced tumor incidence in ErbB2 mice. [55][56][57] Likewise, clinical studies demonstrate that women during or right after pregnancy (when the number of PI-MECs is highest) have increased susceptibility for HER2 breast cancer. 58,59 Thus, we hypothesized that p63 hemizygosity would suppress ErbB2-mediated tumorigenesis as a consequence of a reduced PI-MEC pool.…”
mentioning
confidence: 99%
“…Transgenic mice expressing the wild type Her2/neu (ErbB2) oncogene under transcriptional regulation of the MMTV-LTR seem to be suitable for studying the involvement of PI-MEC in pregnancy-associated mammary tumorigenesis since this animal model exhibits a relatively long latency of tumorigenesis (T50 of 205 days). Using this animal model, we demonstrated that: a) multiparous females consistently exhibited accelerated tumorigenesis compared to their nulliparous littermate controls in a mixed genetic background and b) PI-MEC were, indeed, primary targets of neoplastic transformation in this model [19]. The de novo generation and amplification of a large number of hormone-responsive and apoptosisresistant epithelial cells (i.e.…”
Section: Pi-mec and Mammary Tumorigenesismentioning
confidence: 92%
“…Studies at the molecular level using different platforms for global genome analysis have confirmed the universality of this phenomenon in various strains of rats and mice [13][14][15][16][17][18][19][20][21]. Studies in experimental animal models have been useful for uncovering the sequential genomic changes occurring in the mammary gland in response to multiple hormonal stimuli of pregnancy that lead to the imprinting of a permanent genomic signature.…”
Section: Introductionmentioning
confidence: 99%
“…In these models, the initiation of cancer is prevented by the differentiation of the mammary gland induced by pregnancy [11,12]. The molecular changes involved in this phenomenon are just starting to be unraveled [13][14][15][16][17][18]. The protection conferred by pregnancy is age-specific since a delay in childbearing after age 24 progressively increases the risk of cancer development.…”
Section: Introductionmentioning
confidence: 99%